Applying mucosal barrier injury laboratory-confirmed bloodstream infection criteria in patients with solid tumors and hematologic malignancies: A retrospective cohort study looking for the real source of infection. (11th February 2023) - Puin da Silva, Ana Carolina; Vieira, Michely Fernandes; Freire, Maristela Pinheiro; Vaz, Lumena; Bonazzi, Patrícia Rodrigues; Ibrahim, Karim Yaqub; Diz, Maria Del Pilar Esteves; Hoff, Paulo Marcelo; Pereira, Juliana; Rocha, Vanderson Geraldo; Abdala, Edson
Abstract: We evaluated the interference of the mucosal barrier injury (MBI) laboratory-confirmed bloodstream infection (MBI-LCBI) criteria on the central-line–associated bloodstream infection (CLABSI) incidence density, and the proportion of catheter-related bloodstream infections (CRBSIs) among those classified as MBI. We detected 339 CLABSIs: 15.0% were classified as MBI-LCBIs, and among these, 19.6% were classified as CRBSIs.